Propuesta de implantación, del proceso de planificación del talento humano, para la empresa Planear Construcciones S.A, en la ciudad de Quito, periodo 2023-2024. - Buñay Cuyo, Edwin Javier (2024)
The present research work was carried out in the company Planear Construcciones S.A., with the purpose of developing a proposal for the implementation of the planning process in the human talent area, with the aim of the company having a structural and functional organizational chart, which allows clearly visualizing the number of employees, responsibilities and functions; prevent errors within this process and increase the productivity of workers. The Human Talent Management department of the company Planear Construcciones S.A. does not have the Planning (Organization) subprocess, which is responsible for guaranteeing that the company can have the right number and quality of people. Descriptive research and the deductive methodology were used, so the existing generalities of the company were analyzed, in order to then be able to establish particularities for the human talent area, specifically for the planning subprocess. The DMADV methodology of Six Sigma was used for the development of the new subprocess and the design of operational processes, with which it is intended to increase the productivity of the collaborators of the company Planear Construcciones S.A. Finally, the definition of the human talent management planning subprocess was prepared, which includes the functional and structural organizational charts, a job design according to the needs of the company; as well as the definition of the recruitment and selection, training and development, evaluation and implementation of technological tools subprocesses for the registration of personnel attendance.